STRATEGI PEMANFAATAN MEDIA ALAM SEBAGAI SUMBER BELAJAR UNTUK MENINGKATKAN PEMAHAMAN EKOLOGI SISWA SMP - Ratna Fauziah Azhary; Ahmad Suryadi Naomi (Taksasila Edukasi Insani, 2025)
This study aims to describe the strategy of utilizing natural media as a learning resource to improve ecological understanding among seventh-grade students at SMP Muhammadiyah Cipanas. The background of the research lies in the need for contextual learning that connects science concepts with the students’ surrounding environment to foster meaningful engagement and deeper comprehension. This qualitative descriptive research employed observation, in-depth interviews, and documentation as data collection techniques. The research subjects included science teachers and Grade VII students. The results revealed that the strategy for utilizing natural media involves three main stages: planning environment-based learning, implementing field activities through direct exploration of ecological objects such as soil, plants, and food chains, and evaluation by integrating field reflections with students' cognitive assessments. Natural media effectively increased student enthusiasm, reinforced the connection between theory and practice, and significantly enhanced students’ understanding of ecological concepts. These findings support the relevance of environmentally based learning as an alternative strategy to improve the quality of science education. Keywords : natural media, learning resource, ecology, contextual learning, learning strategy